2021
DOI: 10.3389/fmed.2021.689910
|View full text |Cite
|
Sign up to set email alerts
|

How Free-Viewing Eye Movements Can Be Used to Detect the Presence of Visual Field Defects in Glaucoma Patients

Abstract: Purpose: There is a need for more intuitive perimetric screening methods, which can also be performed by elderly people and children currently unable to perform standard automated perimetry (SAP). Ideally, these methods should also be easier to administer, such that they may be used outside of a regular clinical environment. We evaluated the suitability of various methodological and analytical approaches for detecting and localizing VFD in glaucoma patients, based on eye movement recordings.Methods: The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…However, there was no difference in the fixation duration or rate when watching video clips in either monocular or binocular viewing, nor in the saccadic amplitudes or saccadic velocity. 19 In contrast, Asfaw et al 50 showed that saccades were smaller in amplitude when viewing with the worse glaucomatous eye. The spread of fixations was smaller compared with both control participants and in the better eye.…”
Section: Glaucomamentioning
confidence: 96%
See 4 more Smart Citations
“…However, there was no difference in the fixation duration or rate when watching video clips in either monocular or binocular viewing, nor in the saccadic amplitudes or saccadic velocity. 19 In contrast, Asfaw et al 50 showed that saccades were smaller in amplitude when viewing with the worse glaucomatous eye. The spread of fixations was smaller compared with both control participants and in the better eye.…”
Section: Glaucomamentioning
confidence: 96%
“…The authors commented that, if the goal is to use eye tracking in clinical practice, this preparation time should be reduced significantly. 19 The use of trial lenses in frames to correct vision can pose an additional problem when comparing groups because the trial frame positioned in front of the eyes can restrict the visual field. Therefore, in the study by Smith et al, 48 all participants wore a trial frame, regardless of whether a correction was needed or not, to make sure that each participant had the same limitation.…”
Section: Eye-tracker Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations